Genotoxicity Evaluation of Metformin in Freshwater Planarian Dugesia japonica by the Comet Assay and RAPD Analysis. (17th August 2022) - Yin, Dandan; Xu, Zhenbiao; Feng, Minmin; Zhao, Zelong; Chen, Dahu; Song, Linxia
Abstract : Objective . To investigate the genotoxicity of metformin on planarian with different concentrations and exposure times. Methods . The planarians were treated, respectively, with 10 mmol/L and 50 mmol/L metformin for 1, 3, and 5 days, and then, the comet assay and random amplified polymorphic DNA (RAPD) analysis were performed. 13 random primers were used for PCR amplification with the genomic DNAs as templates. Planarians cultured in clear water were used as the control. Genomic template stability (GTS) was calculated by comparing and analyzing the RAPD patterns of the control group and the treatment groups. Results . In the comet assay, DNA damage of planarians treated with 10 mmol/L metformin for 1, 3, and 5 days was 10.2%, 25.4%, and 36.8%, respectively, and that of planarians treated with 50 mmol/L metformin was 40.6%, 62.8%, and 65.4%, respectively. GTS values of planarians exposed to 10 mmol/L metformin for 1, 3, and 5 days were 64.1%, 62.8%, and 52.6%, respectively, and those of planarians exposed to 50 mmol/L metformin for 1, 3, and 5 days were 52.6%, 51.3%, and 50%, respectively. DNA damage increased and GTS values decreased with the increasing metformin exposure concentration and exposure time. Conclusion . Metformin has certain genotoxicity on planarian in a dose- and time-related manner. The comet assay and RAPD analysis are highly sensitive methods for detecting genotoxicity with drugs.